The Impact of the COVID-19 Pandemic on China's Manufacturing Sector: A Global Value Chain Perspective - Song, Yuegang; Hao, Xiazhen; Hu, Yilin; Lu, Zhou (Frontiers in Public Health, 2021)
This paper, based on the notion of Trade in Value Added (TiVA), links the global trade analysis project (GTAP) model to the value-added model, seeks to simulate and assess the impact of the COVID-19 pandemic on China’s manufacturing sector in global value chain (GVC) reconfiguration. The empirical study provides three major results. First, at the macroeconomic level, the pandemic wreaks a negative impact on all the economies, including the U.S., in regard to import & export trade, GDP and social welfare policy. Second, nation-level simulation shows that there’s a remarkable disparity across different pandemic scenarios in the level of division of labor and of GVC participation for China and its trade partners. Third, sector-level analysis shows that the impacts of the pandemic include promoting the level of GVC participation and of labor division in China’s manufacturing sector (electromechanical equipment and computer goods). This paper also provides policy advice for Chinese government: participation in higher-end GVCs, introduction of further structural reforms and retention of foreign investors, and active responses to GVC reconfiguration and cross-border capital flow.